Labor supply responses and welfare effects from replacing current tax rules by a flat tax: Empirical evidence from Italy, Norway and Sweden - Rolf Aaberge; Ugo Colombino; Steinar Strøm (University of Oslo, Department of Economics, 1998)
This paper employs a microeconometric framework to examine the labor supply responses and the welfare effects from replacing current tax systems in Italy, Norway and Sweden by a flat tax on total income. The flat tax rates are determined so that the tax revenues are equal to the revenues as of 1992. The flat tax rates vary from 23 per cent in Italy, 25 per cent in Norway, to 29 per cent in Sweden. In all three countries the labor supply responses decline sharply with pre-reform disposable income. The results show that the efficiency costs of the current tax systems relative to a flat tax may be rather high in Norway and much lower, but positive, in Italy and Sweden. In all three countries "rich" households - defined by their pre-tax-reform income - tend to benefit more than "poor" households. In Italy and Sweden a majority will lose from a shift to a flat tax, while in Norway a majority is predicted to win.
Keywords: 330